Road Traffic Related Injury Severity in Truck Drivers: A Prospective Medical and Technical Analysis of 582 Truck Crashes - Decker, Sebastian (Arch Trauma Res, 2016)
BACKGROUND: While cyclists and pedestrians are known to be at significant risk for severe injuries when exposed to road traffic accidents (RTA) involving trucks, little is known about RTA injury risk for truck drivers. OBJECTIVES: The aim of this study was to analyze the injury severity in truck drivers following RTAs. PATIENTS AND METHODS: Our local accident research unit prospectively documented 43000 RTAs involving 582 trucks between 2000 and 2011. Injury severity, including the abbreviated injury scale (AIS) and the maximum abbreviated injury scale (MAIS) were analyzed. Technical parameters (e.g. delta-v, direction of impact), the location of accident, and its dependency on the road type were also taken into consideration. RESULTS: Thirteen percent (77/582) of truck drivers were injured. Extremities were found to be at highest risk of injury with the lower extremities (36x) being injured most severely (10x: AIS 2 and 3). Death occurred only after collisions with other trucks, and severity of injuries increased with an increased speed limit. The maximum abbreviated injury scale was higher in the crash opponents (56x MAIS ≥ 3) compared to the truck drivers (8x MAIS ≥ 3). Overall, 82% of the crash opponents were injured. CONCLUSIONS: The safety of truck drivers is assured by their vehicles, the consequence being that the risk of becoming injured is likely to be low. However, the legs especially are at high risk for severe injuries during RTAs. This probability increases in the instance of a collision with another truck. Nevertheless, in RTAs involving trucks and regular passenger vehicles, the other party is in higher risk of injury.